Skin model and some processing properties of a drilling simulation in the abdominal - Colón, Diego (2015)
We know that the skin is a complex organ, and there is a need to measure the complex mechanical properties of the human skin by means of a mathematical representation capable of simulating the deformations that occur during the movements of the body and surgical procedures. We propose for this modeling an analogy between: a) resistance represented by the shock absorber, in this study the modeling will be based on the compression cycle, which occurs once the needle is inserted in the skin, compressing it; b) elasticity given by a spring with a rigidity k; and c) mass, which in turn constitutes the systems inertia resistance to displacement. With the proposed analysis of skin perforation we aim to obtain a model by relating the force applied by the needle to its velocity in the hypodermis. The results shows the steps outlined to convert the analogous system of human skin into a liaison graph, Bond Graph. As discussed by the authors, all data concerning skin are embedded in uncertainty, due especially to the following factors: spatial distribution of the organ, build and dimensions of the individual and lack of specific literature. The skin was thus modeled through a methodology based on the comparison between the real system and a model of the real system. This paper shows the mechanical model that represents skin and the injection in a procedure of abdominal perforation.